Impact of lean manufacturing on the operational performance through industry 4.0 - Ayman Aly Azzab Deghaidy; Salah Mahdy Mohamed Ramadan; Mohamed Mohamed Ahmed Bagha (2024)
The purpose of this study is to investigate and examine the relationship between Lean Manufacturing and the operational performance. It aims at measuring the effect of Kaizen and Total Productive Maintenance as two dimensions of Lean Manufacturing in improving quality, cost, speed, flexibility, and dependability as five dimensions of the operational performance. Also, to check whether Kaizen and Total Productive Maintenance might be moderated by Industry 4.0 technologies. This study tackled only two technologies of Industry 4.0, which are the digitalization of the shop floor, and technologies for vertical and horizontal integration. In addition to the first purpose, this study aimed to check the effectiveness of the implementation of Kaizen activities as one dimension of Lean manufacturing in the Egyptian companies. Two research questions were investigated. The first is what is the relationship between Lean Manufacturing and operational performance? The second is what are Industry 4.0 technologies that can affect the relationship between Lean Manufacturing and operational performance? The sample examined in the study comprised 392 practitioners of Lean Manufacturing activities and systems such as Kaizen and Total Productive Maintenance as well as using Industry 4.0 technologies from several big and medium Egyptian companies. The findings of this study revealed that there is a strong positive correlation between Kaizen and Total Productive Maintenance activities and systems, and the improve of quality, cost, speed, flexibility, and dependability as five dimensions of the operational performance in these Egyptian companies. Also there is a significant effect of the moderator variable "industry 4.0" on the relationship between the independent variable "lean manufacturing" and the dependent variable "operational performance". Furthermore, this study presented and explored ten successful stories and its obtained results in Egypt. It was illustrated how to implement Kaizen philosophy in four industrial sectors "Engineering, Food, Garment, and chemical industries". These cases clarified that small changes (ideas) can affect the productivity a lot. In addition, before and after photos of the improvements are covered in each one of the success stories.
(3GdZQV ef gPg GdOQGSI gh HMK hGNJHGQ GdYdGbI Hjf GdJUfjY GdNGdj ef GdgOQ hGdCOGA GdJTZjdj(B. (3gPg GdOQGSI JgOa Edj bjGS JCKjQ cGjRf hGdUjGfI GdEfJGLjI GdTGedI cCHYGO ddJUfjY GdNGdj ef GdgOQ aj JMSjf GdLhOI hGdJcdaI hGdSQYI hGdeQhfI hGdGYJeGOjI cCHYGO NeSI ddCOGA GdJTZjdj(B. (3CjkVG ddJMbb eeG EPG cGf cGjRf hGdUjGfI GdEfJGLjI GdTGedI ef Gdeecf Cf JOGQ HhGSWI JbfjGJ GdKhQI GdUfGYI GdQGHYI(B. (3gPg GdOQGSI JfGhdJ abW JbfjJjf ef JbfjGJ GdKhQI GdUfGYI GdQGHYI hgeG JbfjGJ QbefI NWhW GdEfJGL , hJbfjGJ GdJcGed GdQCSj hGdCabj(B. (3HGdEVGaI Edi GdZQV GdChd, gOaJ gPg GdOQGSI Edi GdJMbb ef aYGdjI JfajP CfTWI GdJMSjf GdeSJeQ (B((3cGjRf (BKaizen) (3cHYO hGMO ef CHYGO GdJUfjY GdNGdj ef GdgOQ aj GdTQcGJ GdeUQjI(B. (3hdbO Je OQGSI SDGdjf aj GdHMK(B. (3GdChd gh eG gj GdYdGbI Hjf GdJUfjY GdNGdj ef GdgOQ hGdCOGA GdJTZjdj? hGdKGfj gh eG gj JbfjGJ GdKhQI GdUfGYI GdQGHYI GdJj jecf Cf JDKQ Ydi GdYdGbI Hjf GdJUfjY GdNGdj ef GdgOQ hGdCOGA GdJTZjdj? GdYjfI GdJj Je GNJHGQgG aj GdOQGSI TedJ (B392 (3eeGQS dCfTWI hCfXeI GdJUfjY GdNGdj ef GdgOQ eKd cGjRf hGdUjGfI GdEfJGLjI GdTGedI HGdEVGaI Edi GSJNOGe JbfjGJ GdKhQI GdUfGYI GdQGHYI aj YOI TQcGJ eUQjI cHjQI heJhSWI(B. (3CXgQJ fJGFL gPg GdOQGSI Cf gfGc YdGbI EjLGHjI bhjI Hjf CfXeI cGjRf hGdUjGfI GdEfJGLjI GdTGedI hJMSjf GdLhOI hGdJcdaI hGdSQYI hGdeQhfI hGdGYJeGOjI cCHYGO NeSI ddCOGA GdJTZjdj aj gPg GdTQcGJ GdeUQjI(B. (3CjVG jhLO JCKjQ cHjQ ddeJZjQ GdeYOd (B" (3JbfjGJ GdKhQI GdUfGYI GdQGHYI(B" (3Ydi GdYdGbI Hjf GdeJZjQ GdeSJbd (B"(3GdJUfjY GdNGdj ef GdgOQ(B" (3hGdeJZjQ GdJGHY (B"(3GdCOGA GdJTZjdj(B". (3YdGhI Ydi Pdc, bOeJ gPg GdOQGSI hGSJcTaJ YTQ bUU fGLMI hfJGFLgG GdJj Je GdMUhd YdjgG aj eUQ(B. (3hbO Je JhVjM cjajI JfajP adSaI cGjRf aj CQHYI bWGYGJ UfGYjI hgj(B: (3bWGY GdUfGYGJ GdgfOSjI hbWGY GdUfGYGJ GdZPGFjI hbWGY UfGYI GdedGHS hbWGY GdUfGYGJ GdcjejGFjI(B. (3ChVMJ gPg GdMGdGJ Cf GdJZjjQGJ GdUZjQI (B((3GdCacGQ(B) (3jecf Cf JDKQ cKjkQG Ydi GdEfJGLjI(B. (3HGdEVGaI Edi Pdc, ZWJ UhQ GdJMSjfGJ bHd hHYO YedjGJ GdJMSjf aj cd hGMOI ef bUU GdfLGM(B.s
Thesis (Ph.D)-Cairo University, 2024.
Bibliography: pages 157-168.
Issues also as CD.
Text in English and abstract in Arabic & English.
Keywords: Quality Control; Lean Manufacturing -- Operational Performance -- Industry 4.0